Manajemen Bimbingan Konseling Dalam Meningkatkan Penguasaan Keterampilan Layanan Konseling Guru Bk - Sabrial, Jumli; Hayati, Rida; Dasril (Conseils : Jurnal Bimbingan dan Konseling Islam, 2025)
To achieve success in the implementation of guidance and counseling, more focused management services are needed so that goals can be achieved optimally. This study aims. This study aims to analyze more deeply related to guidance and counseling management in improving the mastery of counseling service skills of BK teachers. This study uses a literature study method with a descriptive normative approach, relying on primary data, namely POP BK, as well as secondary data from books and articles. Data were collected through documentation techniques and analyzed using content analysis methods to obtain valid conclusions. One of the management process models that can help explain various problems is through reflective analysis of the contents of counseling sessions. The main focus of guidance and counseling lies on the client, by analyzing what is conveyed, how aspects of the client's life are interconnected, and what the client wants. Information expressed by the client can also be a guide for BK teachers in understanding cases that may not have been explicitly realized. It is hoped that this study can be used as a consideration for related science.